Maternal educational attainment in pregnancy and epigenome-wide DNA methylation changes in the offspring from birth until adolescence$article - Choudhary, Priyanka; Monasso, Giulietta S.; Karhunen, Ville; Ronkainen, Justiina; Mancano, Giulia; Howe, Caitlin G.; Niu, Zhongzheng; Zeng, Xuehuo; Guan, Weihua; Dou, John; Feinberg, Jason I.; Mordaunt, Charles; et al. (Molecular psychiatry, 2023)
Maternal educational attainment (MEA) shapes offspring health through multiple potential pathways. Differential DNA methylation may provide a mechanistic understanding of these long-term associations. We aimed to quantify the associations of MEA with offspring DNA methylation levels at birth, in childhood and in adolescence. Using 37 studies from high-income countries, we performed meta-analysis of epigenome-wide association studies (EWAS) to quantify the associations of completed years of MEA at the time of pregnancy with offspring DNA methylation levels at birth (n = 9 881), in childhood (n = 2 017), and adolescence (n = 2 740), adjusting for relevant covariates. MEA was found to be associated with DNA methylation at 473 cytosine-phosphate-guanine sites at birth, one in childhood, and four in adolescence. We observed enrichment for findings from previous EWAS on maternal folate, vitamin-B12 concentrations, maternal smoking, and pre-pregnancy BMI. The associations were directionally consistent with MEA being inversely associated with behaviours including smoking and BMI. Our findings form a bridge between socio-economic factors and biology and highlight potential pathways underlying effects of maternal education. The results broaden our understanding of bio-social associations linked to differential DNA methylation in multiple early stages of life. The data generated also offers an important resource to help a more precise understanding of the social determinants of health.
Gesehen am 07.02.2024